Thus spake the dervish : Sufism, language, and the religious margins in Central Asia, 1400-1900 - Papas, Alexandre, (Impact of Empire;, 2019)
Thus Spake the Dervish explores the unfamiliar history of marginal Sufis, known as dervishes, in early modern and modern Central Asia over a period of 500 years. It draws on various sources (Persian chronicles and treatises, Turkic literature, Russian and French ethnography, the author's fieldwork) to examine five successive cases, each of which corresponds to a time period, a specific socially marginal space, and a particular use of mystical language. Including an extensive selection of writings by dervishes, this book demonstrates the diversity and tenacity of Central Asian Sufism over a long period. Here translated into a Western language for the first time, the extracts from primary texts by marginal Sufis allow a rare insight into their world. The original French edition of this book, Ainsi parlait le dervice, was published by Editions du Cerf (Paris, France). Translated by Caroline Kraabel.